A propensity score matching study between ultrasound-guided percutaneous microwave ablation and conventional thyroidectomy for benign thyroid nodules treatment. (31st December 2018) - Jin, Hao; Fan, Jinrui; Liao, Kun; He, Zhuocheng; Li, Wei; Cui, Min
Abstract: Purpose: Our study aims to compare ultrasound (US)-guided percutaneous microwave ablation (PMWA) and conventional thyroidectomy in benign thyroid nodules (BTN) treatment. Materials and methods: From December 2015 to December 2017, a total of 280 patients with at least one benign thyroid nodule were studied retrospectively, including 156 patients treated with US-guided PMWA and 124 patients treated with conventional thyroidectomy. Propensity score matching was performed to decrease the confounding bias due to retrospective assignment and to balance the pre-operation data of the two groups. A total of 106 pairs (1:1) was created. The operation time, intraoperative blood loss, postoperative hospitalization time, serum levels of interleukin (IL-6), C-reactive protein (CRP), tumor necrosis factor-α (TNF-α) 12 h after operation and postoperative complications incidence rate were compared between the two groups. The volume reduction ratio was calculated in the US-guided PMWA group at 1, 3, 6 and 12 months after treatment. Registration number: ChiCTR1800015531. Results: Significant differences were found between the two groups in levels of CRP, IL-6, and TNF-α after the operation； there were significant differences between the two groups in intraoperative blood loss, operation time, postoperative hospitalization time and postoperative complications rate. The volume reduction ratio at 1, 3, 6 and 12 months after treatment was 15.2%, 47.6%, 67.2% and 79.6%, respectively. Conclusions: Our study demonstrated that US-guided PMWA is characterized by a definite therapeutic success rate, good cosmetic effect, slight injury and rapid recovery. US-guided PMWA is an effective technique for benign thyroid nodules treatment．